2020
DOI: 10.4314/ejhs.v30i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Immunological Detection of Mycobacterium Tuberculosis from HIV and Non-HIV Patients in Benue State, Nigeria

Abstract: BACKGROUND: Immunological techniques are important tools for tuberculosis epidemiology; although its use is underutilized in Nigeria. In this study, we report the epidemiological outlook of Mycobacterium tuberculosis among HIV patients in Benue State, Nigeria.METHODS: Sputum samples were collected from 425 suspected TB patients from July 2016 to February 2018 and subjected to acid-fast microscopy, GeneXpert MTB/RIF, processed using NALC-NaOH and cultured on Lowenstein-Jensen media. The isolates obtained were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
0
2
Order By: Relevance
“…The association was not statistically significant (p = 0.113). The finding from this study is dissimilar to findings from studies including in Benue state Nigeria which showed that the prevalence of TB significantly (χ 2 = 8.458; P = 0.003) highest in the 15-34 years age group (22.0%) compared to other age groups [26]. Also, in Port Harcourt Nigeria, the age-specific infection rate had a higher Tb in the age group >25 years (2.8%) than in <25 years (2.3%) and Age was the main correlate (P<0.05) of TB [39].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The association was not statistically significant (p = 0.113). The finding from this study is dissimilar to findings from studies including in Benue state Nigeria which showed that the prevalence of TB significantly (χ 2 = 8.458; P = 0.003) highest in the 15-34 years age group (22.0%) compared to other age groups [26]. Also, in Port Harcourt Nigeria, the age-specific infection rate had a higher Tb in the age group >25 years (2.8%) than in <25 years (2.3%) and Age was the main correlate (P<0.05) of TB [39].…”
Section: Discussioncontrasting
confidence: 99%
“…= 0.043 -0.141). The finding from this study agrees with a study from Benue state Nigeria which showed that the prevalence of TB was significantly (χ2 = 4.751; P = 0.029) higher in rural areas than urban areas amongst patients (23.8% vs 14.1%) [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation